Dual specificity phosphatase 5 and 6 are oppositely regulated in human skeletal muscle by acute exercise. Issue 19 (9th October 2017) - Pourteymour, Shirin; Hjorth, Marit; Lee, Sindre; Holen, Torgeir; Langleite, Torgrim M.; Jensen, Jørgen; Birkeland, Kåre I.; Drevon, Christian A.; Eckardt, Kristin
Abstract: Physical activity promotes specific adaptations in most tissues including skeletal muscle. Acute exercise activates numerous signaling cascades including pathways involving mitogen‐activated protein kinases (MAPKs) such as extracellular signal‐regulated kinase (ERK)1/2, which returns to pre‐exercise level after exercise. The expression of MAPK phosphatases (MKPs) in human skeletal muscle and their regulation by exercise have not been investigated before. In this study, we used mRNA sequencing to monitor regulation of MKPs in human skeletal muscle after acute cycling. In addition, primary human myotubes were used to gain more insights into the regulation of MKPs. The two ERK1/2‐specific MKPs, dual specificity phosphatase 5 (DUSP5) and DUSP6, were the most regulated MKPs in skeletal muscle after acute exercise. DUSP5 expression was ninefold higher immediately after exercise and returned to pre‐exercise level within 2 h, whereas DUSP6 expression was reduced by 43% just after exercise and remained below pre‐exercise level after 2 h recovery. Cultured myotubes express both MKPs, and incubation with dexamethasone (Dex) mimicked the in vivo expression pattern of DUSP5 and DUSP6 caused by exercise. Using a MAPK kinase inhibitor, we showed that stimulation of ERK1/2 activity by Dex was required for induction of DUSP5 . However, maintaining basal ERK1/2 activity was required for basal DUSP6 expression suggesting that the effect of Dex on DUSP6 might involve an ERK1/2‐independent mechanism. We conclude that the altered expression of DUSP5 and DUSP6 in skeletal muscle after acute endurance exercise might affect ERK1/2 signaling of importance for adaptations in skeletal muscle during exercise. Abstract : Acute exercise oppositely alters dual specificity phosphatase 5 ( DUSP5 ) and DUSP6 mRNA expression in human muscle. Dexamethasone (Dex) mimics this pattern in vitro in primary human myotubes. Extracellular signal‐regulated kinase (ERK)1/2 activity is required for DUSP5 induction by Dex. Repression of DUSP6 by Dex is independent of its effect on ERK1/2 activity.